Biosynthesis of rhizocticins, antifungal phosphonate oligopeptides produced by Bacillus subtilis ATCC6633 - Borisova, Svetlana A. (2010)
Rhizocticins are phosphonate oligopeptide antibiotics containing the C-terminal non-proteinogenic amino acid (Z)-l-2-amino-5-phosphono-3-pentenoic acid (APPA). Here we report the identification and characterization of the rhizocticin biosynthetic gene cluster (rhi) in Bacillus subtilis ATCC6633. Rhizocticin B was heterologously produced in the non-producer strain Bacillus subtilis 168. A biosynthetic pathway is proposed based on bioinformatics analysis of the rhi genes. One of the steps during the biosynthesis of APPA is an unusual aldol reaction between phosphonoacetaldehyde and oxaloacetate catalyzed by an aldolase homolog RhiG. Recombinant RhiG was prepared and the product of an in vitro enzymatic conversion was characterized. Access to this intermediate allows for biochemical characterization of subsequent steps in the pathway.